A hemostatic material and a method of making the same
Patent Information
- Application Number
- CN202311158011.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-09-08
AI Technical Summary
[0006]本发明的目的是针对现有临床使用的止血海绵存在吸收性不高,止血效率低,生物相容性差、力学性能弱等技术问题,提供一种止血材料及其制备方法,本发明的止血材料对流体吸收率高,止血时间短,失血量显著降低;吸水率和吸水速率高,且吸水后可快速膨胀,迅速堵住伤口;在创口处快速吸液,加速血小板和红细胞的聚集,快速止血;本发明的止血材料的生物相容性、抗菌性能和凝血性能好,在伤口凝血止血、组织修复等生物医学应用方面具有应用前景
[0034]本发明创制的止血海绵的具有较高的流体吸收率、优异的形状记忆性能和较强的机械弹性;在生物学性能方面,该海绵的全血凝血指数更低,血细胞和血小板的聚集能力更强;大鼠股动脉损伤模型和肝容量缺损损伤模型实验表明,海绵的止血时间显著少于已有商品明胶海绵;此外,该海绵对金色葡萄球菌和大肠杆菌表现出较好的抑菌效果,其生物相容性和血液相容性良好。综合评价,紫胶-明胶复合海绵状多功能止血材料在大出血病例中有巨大应用潜力,可满足日常生活及医疗中的出血应急处理。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a medical material and its preparation method, particularly to a medical hemostatic material and its preparation method, belonging to the field of biomedical materials technology. Background Technology
[0002] Traditionally, gauze and bandages are the primary hemostatic materials for quickly controlling bleeding. To improve the hemostatic effect of traditional gauze, many substances with coagulation properties, such as thrombin, protamine sulfate, ethamsylate, aminocaproic acid, tranexamic acid, and tranexamic acid, have been used. Currently, products such as Combat gauze, HemCon bandages, and Surgicel are available on the market. Although these products have significant hemostatic capabilities for superficial injuries, experimental results show that most products cannot handle severe bleeding cases, especially irregular, uncontrollable, and non-compressible traumatic bleeding. Therefore, the development of hemostatic materials suitable for massive bleeding is crucial.
[0003] Hemostatic materials are obtained by chemically modifying active ingredients or processing them into a specific form. However, developing methods to imbue active ingredients with more useful wound-healing properties without affecting their hemostatic behavior remains a challenge. To date, many novel hemostatic materials have been developed by chemically modifying active ingredients or processing them into a specific form, ranging from simple to complex, from 2D to 3D, from hydrophilic to hydrophobic, and from macroscopic to nanoscale. The morphology of hemostatic materials influences their function and application, with the most widely used forms being sponges, hydrogels, nanofibers, and particles or powders. In contrast, sponge materials are more attractive due to their shape recovery properties and liquid absorption capacity, which may offer advantages in dealing with some atypical wounds. They can be injected in sponge form under compression, allowing them to rapidly expand and fully contact irregular bleeding wounds. For example, Zhang et al. developed an injectable hemostatic sponge based on nanocellulose, characterized by high water absorption, rapid shape recovery, and strong antibacterial properties. Guo et al. prepared a hybrid hemostatic sponge with high mechanical properties and excellent shape memory ability using polyvinyl alcohol, carboxymethyl chitosan, and dopamine to address lethal incompressible bleeding. Currently, absorbable gelatin sponges are the most commonly used hemostatic material in clinical practice. They are non-toxic, non-antigenic protein gels with a porous structure, capable of absorbing more than 30 times their own body volume in fluids and blood. Furthermore, the presence of positron-coated deposits within the gelatin sponge facilitates the adsorption of platelets, leading to the formation of small thrombi at the site of hemostasis. However, the clinical use of absorbable gelatin sponges still faces challenges such as low hemostatic efficiency, poor biocompatibility, and weak mechanical properties.
[0004] Lac is a natural resin secreted by lac insects. Its molecular structure contains long-chain hydroxy fatty acids and sesquiterpene acids, thus giving it good film-forming properties, tissue adhesion, and biocompatibility.
[0005] This invention uses bleached shellac and gelatin as raw materials to prepare a sponge-like multifunctional hemostatic material; it is also compounded with the polyphenol compound propyl gallate, which can further improve the material's blood adsorption, hemostatic and antibacterial properties. Summary of the Invention
[0006] The purpose of this invention is to address the technical problems of existing clinically used hemostatic sponges, such as low absorbency, low hemostatic efficiency, poor biocompatibility, and weak mechanical properties, by providing a hemostatic material and its preparation method. The hemostatic material of this invention has high fluid absorption rate, short hemostatic time, and significantly reduced blood loss; it has high water absorption rate and absorption speed, and can rapidly expand after absorbing water to quickly seal the wound; it rapidly absorbs fluid at the wound site, accelerating the aggregation of platelets and red blood cells for rapid hemostasis; the hemostatic material of this invention has good biocompatibility, antibacterial properties, and coagulation properties, and has promising applications in biomedical fields such as wound coagulation and hemostasis, and tissue repair.
[0007] To achieve the objectives of this invention, one aspect of this invention provides a hemostatic material, including gelatin and shellac.
[0008] The weight ratio of gelatin to shellac is (0.05-1):1, preferably (0.2-0.3):1, and more preferably 0.2:1.
[0009] In particular, it also includes a hemostatic enhancer, which is selected from gallic acid or gallic acid derivatives.
[0010] In particular, the gallic acid derivative is selected from propyl gallate, gallic acid, gallotannic acid, methyl gallate, lauryl gallate, hexadecyl gallate, octadecyl gallate, and octadecyl gallate, and is preferably propyl gallate and gallotannic acid.
[0011] In particular, the weight ratio of the hemostatic enhancer to shellac is (0.02-0.1):1, preferably 0.04:1.
[0012] In particular, the weight ratio of the hemostatic enhancer propyl gallate to shellac is (0.02-0.1):1, preferably 0.04:1.
[0013] Another aspect of the present invention provides a method for preparing a hemostatic material, comprising the following steps performed in sequence:
[0014] 1) Add gelatin to the shellac solution, heat, stir and dissolve to prepare a shellac-gelatin solution;
[0015] 2) The shellac-gelatin solution was freeze-dried to obtain a hemostatic material.
[0016] In particular, the volume ratio of the shellac solution to the mass of the gelatin in step 1) is 10:(0.05-1), preferably 10:(0.2-0.3), and more preferably 10:0.2.
[0017] In particular, in step 1), the weight ratio of gelatin to shellac in the shellac-gelatin solution is (0.05-1):1, preferably (0.2-0.3):1, and more preferably 0.2:1.
[0018] In particular, the shellac solution is a shellac ammonia solution, prepared by adding bleached shellac to an ammonia solution, heating, and stirring to dissolve.
[0019] In particular, the mass percentage concentration of the ammonia solution is 0.1-0.5%, preferably 0.2%.
[0020] In particular, the mass-volume concentration of the shellac solution is 0.05-0.2 g / mL, that is, 0.05-0.2 g of shellac is dissolved in 1 mL of ammonia water, preferably 0.1 g / mL.
[0021] In particular, the heating temperature is 40-60℃, preferably 50℃.
[0022] In step 2), during the freeze-drying process, the temperature is controlled at -50 to -10℃, preferably -40℃; the relative pressure is 20 to 70 Pa, preferably 40 Pa; and the freeze-drying time is 60 to 80 h, preferably 72 h.
[0023] Another aspect of the present invention provides a method for preparing a hemostatic material, comprising the following steps performed in sequence:
[0024] 1) Add gelatin to the shellac solution, heat, stir and dissolve to prepare a shellac-gelatin solution;
[0025] 2) Add a hemostatic enhancer to the shellac-gelatin solution, stir and mix evenly to prepare a shellac-gelatin-enhancer mixture system, wherein the hemostatic enhancer is selected from gallic acid or gallic acid derivatives;
[0026] 3) The shellac-gelatin-reinforcing agent mixture was freeze-dried to obtain a hemostatic material.
[0027] In step 2), the amount of hemostatic enhancer added is 20-100 mg per 10 mL of shellac-gelatin solution, preferably 40 mg per 10 mL of shellac-gelatin solution.
[0028] In particular, the hemostatic enhancer is selected from propyl gallate, gallic acid, gallotannic acid, methyl gallate, lauryl gallate, hexadecyl gallate, octadecyl gallate, and octadecyl gallate, preferably propyl gallate and gallotannic acid.
[0029] In particular, the amount of the hemostatic enhancer propyl gallate added is 20-100 mg per 10 mL of shellac-gelatin solution, preferably 40 mg per 10 mL of shellac-gelatin solution.
[0030] In particular, the weight ratio of the hemostatic enhancer added in step 2) to shellac is (0.02-0.1):1, preferably 0.04:1.
[0031] In particular, the weight ratio of the hemostatic enhancer propyl gallate to shellac is (0.02-0.1):1, preferably 0.04:1.
[0032] In particular, during the freeze-drying process in step 3), the temperature is controlled at -50 to -10°C, preferably -40°C; the relative pressure is 20 to 70 Pa, preferably 40 Pa; and the freeze-drying time is 60 to 80 h, preferably 72 h.
[0033] This invention uses bleached shellac and gelatin as raw materials to prepare a sponge-like multifunctional hemostatic material through their cross-linking reaction. The material is then compounded with the polyphenol compound propyl gallate to improve its blood adsorption, hemostatic and antibacterial properties.
[0034] The hemostatic sponge developed in this invention possesses high fluid absorption rate, excellent shape memory properties, and strong mechanical elasticity. In terms of biological properties, the sponge exhibits a lower whole blood coagulation index and stronger aggregation ability of blood cells and platelets. Experiments using rat femoral artery injury models and liver volume defect models show that the sponge's hemostasis time is significantly shorter than that of existing commercial gelatin sponges. Furthermore, the sponge demonstrates good antibacterial effects against Staphylococcus aureus and Escherichia coli, and exhibits good biocompatibility and blood compatibility. In summary, this shellac-gelatin composite sponge-like multifunctional hemostatic material has great application potential in cases of massive bleeding and can meet the needs of emergency bleeding management in daily life and medical settings.
[0035] Compared with the prior art, the present invention has the following advantages and benefits:
[0036] 1. The hemostatic sponge of the present invention has a rich porous structure, which is conducive to the rapid entry and absorption of fluids, thereby promoting blood concentration and rapid thrombus formation.
[0037] 2. The hemostatic sponge of this invention can be easily customized into various shapes to adapt to different wounds; it still exhibits excellent shape memory function and mechanical properties even after being repeatedly compressed 20 times under high pressure, and therefore has great potential for application in narrow, irregular and incompressible wounds.
[0038] 3. The hemostatic sponge of this invention has excellent hydrophilic and hydrophobic synergistic effect, and can absorb about 10 times its own weight of liquid in a very short time.
[0039] 4. The hemostatic sponge of the present invention has good coagulation ability and can adhere well to red blood cells and platelets; the hemolysis rate is less than 3.5%, which meets the application safety standards for hemostatic sponges; in vivo and in vitro tests show that the sponge has good biocompatibility.
[0040] 5. The hemostatic sponge of the present invention has a good hemostatic effect on the femoral artery injury and massive bleeding model, and the hemostatic rate is better than that of existing commercial gelatin sponges. Moreover, the sponge can also be used for hemostasis of internal organs such as the liver. Attached Figure Description
[0041] Figure 1 The infrared spectrum of the hemostatic sponge is shown below.
[0042] Figure 2 XRD pattern of the hemostatic sponge;
[0043] Figure 3 SEM image of the hemostatic sponge;
[0044] Figure 4A The density test results of the hemostatic sponge sample are shown in the figure.
[0045] Figure 4B This is a statistical graph of the porosity of the sponge sample;
[0046] Figure 5 The graph shows the results of the compressibility deformation test of SNPG sponge and gelatin.
[0047] Figure 6A shows the volume expansion rate test diagram of the sponge after absorbing liquid;
[0048] Figure 6B Photographs of sponges of different shapes made from the SNPG0.2 sponge prepared in Example 3;
[0049] Figure 7A A graph showing the volume recovery rate of a sponge after absorbing liquid and then squeezing it.
[0050] Figure 7B Compression cycle diagram of the SNPG0.2 sponge prepared in Example 3;
[0051] Figure 7C Compression cycle diagram of the SNPG0.6 sponge prepared in Example 7;
[0052] Figure 8A The results show the water absorption rate of the sponge sample.
[0053] Figure 8B The results of the blood absorption rate test for the sponge sample;
[0054] Figure 9 A test chart showing the time required for complete absorption of droplets on the surface of a hemostatic sponge;
[0055] Figure 10A BCI statistic of hemostatic sponge;
[0056] Figure 10B A statistical chart of clotting time of hemostatic sponges (where: *, p < 0.05; **, p < 0.01; ***, p < 0.001).
[0057] Figure 11 Statistical chart of the adhesion rate of hemostatic sponges to erythrocytes;
[0058] Figure 12 The images show the adhesion of red blood cells to sponge samples, where A is a gauze sample; B is an SN sample; C is a PG sample; B is an SNPG0.2 sample; and D is a commercial gelatin sponge.
[0059] Figure 13 A statistical graph of platelet adhesion rate in hemostatic sponge samples;
[0060] Figure 14A Statistical results of hemolysis rate in hemostatic sponge samples;
[0061] Figure 14B Images of hemolytic sponge samples; where a is the positive control, b is SNG, c is SNPG 0.1, d is SNPG 0.2, e is SNPG 0.3, f is SNPG 0.4, g is SNPG 0.5, h is PG, i is gauze, j is commercial gelatin sponge, and k is the negative control;
[0062] Figure 15 The survival rate of NIH-3T3 cells after treatment with different sponge samples;
[0063] Figure 16A A stained section of wound tissue 7 days after sponge sample implantation;
[0064] Figure 16BPhotographs showing the inhibitory effect of sponge samples on Staphylococcus aureus and Escherichia coli;
[0065] Figure 16C A statistical graph showing the antibacterial rate of sponge samples;
[0066] Figure 17A Statistical chart of blood loss during hemostatic sponge treatment of femoral puncture wound bleeding (n≥3) (where: *, p< 0.05; **, p < 0.01; ***, p < 0.001).
[0067] Figure 17B Statistical graph of hemostasis time (n≥3) during hemostasis sponge treatment of femoral puncture wound bleeding (where: *, p < 0.05; **, p < 0.01; ***, p < 0.001). Detailed Implementation
[0068] The present invention will be further described below with reference to specific embodiments, and the advantages and features of the present invention will become clearer as a result. However, these embodiments are merely exemplary and do not constitute any limitation on the scope of the present invention. Those skilled in the art should understand that modifications or substitutions can be made to the details and form of the technical solutions of the present invention without departing from the spirit and scope of the present invention, but all such modifications and substitutions fall within the protection scope of the present invention.
[0069] Example 1
[0070] 1. Prepare shellac solution
[0071] Bleached shellac is added to an ammonia solution, heated in a water bath, and stirred to dissolve, thus preparing a shellac ammonia solution (SN solution). The mass percentage concentration of the ammonia solution is 0.2% (usually 0.1-0.5%), and the mass volume concentration of the shellac ammonia solution is 0.1 g / mL (usually 0.05-0.2 g / mL), meaning that 0.1 g of bleached shellac is present in every 1 mL of ammonia solution. The water bath heating temperature is 50℃ (usually 45-60℃).
[0072] 50.0 g of bleached shellac was added to 500 mL of a 0.2% (w / w) ammonia solution and dissolved in a water bath at 50°C for 1.5 h to obtain a concentration of 0.1 g / mL. -1 Ammonia solution of shellac (named SN solution).
[0073] 2. Prepare shellac-gelatin mixture
[0074] Gelatin is added to a prepared shellac ammonia solution (SN solution), and the mixture is heated and stirred to dissolve, thus preparing a shellac-gelatin mixture. The mass ratio of gelatin to the volume of the shellac ammonia solution is 0.05:10 (usually (0.05-1):10), and the volume ratio of the shellac ammonia solution to the mass of gelatin is 10:0.05, meaning 0.05g of gelatin is added to every 10mL of the shellac ammonia solution. The weight ratio of gelatin to shellac in the shellac-gelatin mixture is 0.05:1 (usually (0.05-1):1), preferably (0.2-0.3):1, and more preferably 0.2:1.
[0075] Take 10 mL of SN solution and add different masses of gelatin to it. Stir and react at 50℃ for 2 h. Add 0.05, 0.10, 0.20, 0.30, 0.40, 0.50 and 0.60 g of gelatin to each 10 mL of SN solution.
[0076] 3. Prepare a shellac-gelatin-reinforcing agent mixture system
[0077] Add propyl gallate (PG), a hemostatic enhancer, to the shellac-gelatin mixture, stir and mix thoroughly to prepare a shellac-gelatin-enhancer mixture system (SNPG mixture system). The amount of propyl gallate added is 40 mg per 10 mL of shellac-gelatin mixture (usually 40-100 mg per 10 mL of shellac-gelatin mixture, preferably 40 mg). The weight ratio of shellac to propyl gallate in the shellac-gelatin-gallic acid mixture system is 1:0.04 (usually 1:(0.02-0.1, preferably 1:0.04).
[0078] The purpose of adding propyl gallate in this invention is to enhance the hemostatic and coagulant properties of the shellac-gelatin sponge, while also enhancing its antibacterial properties and promoting wound healing. After addition, propyl gallate is linked to the shellac-gelatin network through hydrogen bonding, forming a mesh-like, porous structure.
[0079] Besides propyl gallate, other hemostatic enhancers such as gallic acid, gallotannic acid, methyl gallate, lauryl gallate, hexadecyl gallate, octadecyl gallate, and octadecyl gallate are also applicable to this invention. The specific embodiments of this invention are described using propyl gallate as an example.
[0080] 4. Freeze-drying treatment
[0081] The prepared shellac-gelatin-gallic acid mixture was freeze-dried to obtain a hemostatic sponge (SNPG0.05 sponge). During the freeze-drying process, the temperature was controlled at -40℃, the pressure at 40 Pa, and the time at 72 h.
[0082] Take 3.0 mL of the prepared shellac-gelatin-reinforcing agent mixture and place it in a cylindrical mold with an inner diameter of 20 mm and a height of 20 mm. Place the mold in a freeze dryer for freeze drying. The freeze drying process conditions are as follows: freeze drying temperature is -40℃; relative pressure is 40 Pa; freeze drying time is 72 h.
[0083] In the freeze-drying process of preparing the hemostatic sponge according to the present invention, the temperature is controlled at -50 to -10℃, preferably -40℃; the relative pressure is 20 to 70 Pa, preferably 40 Pa; and the freeze-drying time is 60 to 80 h, preferably 72 h.
[0084] Examples 2-7
[0085] Except for the mass-to-volume ratios of the shellac-gelatin mixture in step 2) being 0.10:10, 0.20:10, 0.30:10, 0.40:10, 0.50:10, and 0.60:10 respectively; the shellac-gelatin-gallic acid mixtures prepared in step 3) being abbreviated as SNPG0.1, SNPG0.2, SNPG0.3, SNPG0.5, and SNPG0.6 respectively; and the hemostatic sponges prepared in step 4) being abbreviated as SNPG0.1, SNPG0.2, SNPG0.3, SNPG0.5, and SNPG0.6 sponges respectively, the rest are the same as in Example 1.
[0086] Compare with Example 1
[0087] Except for step 2), where the mass-to-volume ratio of the shellac-gelatin mixture is 0.2:10, and step 3), where propyl gallate is not added to the shellac-gelatin mixture, the rest is the same as in Example 1. The sample group without added PG is designated as SNG sponge.
[0088] Compare with Examples 1A-1E
[0089] Except for step 2), where the mass-to-volume ratio of the shellac-gelatin mixture is 0.10:10, 0.30:10, 0.40:10, 0.50:10, and 0.60:10 respectively, and propyl gallate is not added to the shellac-gelatin mixture (i.e., step 3) is not performed, everything else is the same as in Example 1. The sample group without added PG is designated as SNG sponge.
[0090] Compare with Example 2
[0091] The shellac ammonia solution (SN solution) prepared in step 1) of Example 1 was freeze-dried using the same freeze-drying process as in step 4) of Example 1 to obtain a sponge (hereinafter referred to as SN sponge sample).
[0092] Experimental Example 1: Structural Characterization of Hemostatic Sponge Samples
[0093] 1. Infrared spectrum
[0094] The SNPG0.2 sponge prepared in Example 3, the SNG sponge prepared in Control Example 1, the SN solid sample prepared in Control Example 2, gelatin, propyl gallate, and shellac were subjected to infrared spectroscopy. The infrared spectra are shown below. Figure 1 As shown.
[0095] Compared to shellac, SN solid samples at 1558 cm⁻¹ -1 An absorption peak for the stretching vibration of a C=N bond is added at 3200 cm⁻¹. -1 The absorption peak at the point becomes broad and strong, indicating that when shellac is dissolved in ammonia, its aldehyde group undergoes an addition reaction with ammonia to generate a product with an imine structure.
[0096] Gelatin molecules contain a large number of carboxyl and amino groups. When it and a small amount of propyl gallate are added to an ammonia solution of shellac and heated for 2 hours, the resulting SNPG sponge sample shows a concentration of 1654 cm⁻¹. -1 and 1731 cm -1 There are two strong absorption peaks, indicating that a chemical cross-linking reaction occurred between shellac and gelatin, generating a large number of amide bonds and ester bonds; after the addition of propyl gallate, it is linked in the shellac-gelatin network through hydrogen bonding.
[0097] 2. X-ray diffraction
[0098] X-ray diffraction was performed on the hemostatic sponges prepared in Examples 2-4, the SN solid samples, and the gelatin used in Examples 1-7 to test the crystal information of the samples. The results are as follows: Figure 2 .
[0099] like Figure 2 The diffraction peaks of the three sponge samples tested (i.e., SNPG0.1, 0.2, and 0.3 sponge samples) basically overlapped, with a broad amorphous peak appearing at around 19.8°. Compared with SN, the peak width of SNPG was narrower, indicating that their aggregation morphology tended to be a more regular and ordered structure.
[0100] 3. Scanning electron microscopy
[0101] The morphology of the SN solid samples, the hemostatic sponges prepared in Examples 2-7, and the gelatin was observed using an electron microscope (SEM). The observation results are as follows: Figure 3As shown. From the appearance, the SN sample is loose and will crumble easily with a light touch; the scan image shows:
[0102] The SN samples exhibited a scale-like accumulation forming continuous grooves and ridges, lacking a distinct porous structure. Upon adding gelatin to the SN samples, all SNG sponges developed a porous structure. SNPG0.1, with a lower gelatin content, showed an unevenly distributed porous structure, making it prone to collapse and deformation under external forces. SNPG0.2 and SNPG0.3 sponges displayed interconnected macroporous structures with pore sizes ranging from 212.5 to 425.3 μm. Subsequently, with increasing gelatin content, the number of pores per unit volume increased in SNPG0.4 and SNPG0.5 sponges, but the average pore size gradually decreased. Further increases in gelatin content resulted in a denser sponge with only a few visible pores. This is likely due to the increased cross-linking between shellac and gelatin with the increased gelatin content. As a control, commercial gelatin sponges displayed a rich, interwoven porous structure.
[0103] Experimental Example 2: Density Test of Hemostatic Sponge Samples
[0104] 1.2 Density test of sponge samples
[0105] 3 mL each of the SNPG sample (i.e., the shellac-gelatin-propyl gallate mixture) prepared in step 3) of Examples 1-7 and the SN solution prepared in step 1) of Example 1 were injected into cylindrical molds; then, the sponge test samples were obtained by freeze-drying. The mass (m0), diameter (R), and height (H) of the sponge test samples were accurately weighed and measured, and the density of each test sample was calculated using formula (1):
[0106] (1)
[0107] Density test results as follows Figure 4A As shown in the figure, it can be seen that as the amount of gelatin added to SNPG increases, the density of the resulting sponge also gradually increases.
[0108] Experimental Example 3: Porosity Test of Hemostatic Sponge Samples
[0109] The hemostatic sponges prepared in Examples 1-7 were weighed beforehand, and their weights before immersion in water (W0, g) were recorded. Then, each accurately weighed sponge was immersed in deionized water for 30 minutes. After immersion, the sponges were removed and weighed again after absorbing water (W1, g). Finally, the volume of the hemostatic sponge after absorbing water (V, cm³) was measured. -3 Then, calculate the porosity (%) of the hemostatic sponge according to formula (2).
[0110] (2)
[0111] In formula (2): W0 and W1 are the weights (g) of the hemostatic sponge before and after soaking in water; ρ is the density of water (1.0 g·cm³). -3 V represents the volume of the hemostatic sponge after absorbing water. All hemostatic sponge samples were measured five times.
[0112] During sample preparation, a circular mold with an inner diameter of 20 mm and a height of 20 mm was used, so the prepared sample was cylindrical. The diameter R and height H after water absorption were measured with vernier calipers to obtain the volume V of the sponge sample after water absorption.
[0113] Results of hemostatic sponge porosity measurement are as follows Figure 4B , Figure 4B The porosity of the SNPG sponge shows an inverse trend compared to its density, gradually decreasing with increasing gelatin content. The porous structure of the sponge facilitates rapid fluid entry and absorption. Simultaneously, a suitable pore size promotes the accumulation of blood components within the pores, forming thrombi and thus promoting blood coagulation. On one hand, when all the surface pores of the hemostatic sponge are closed, it hinders the entry of blood cells. On the other hand, when the pore diameter of the hemostatic sponge is too large, more blood cells are needed to form microthrombi, which is detrimental to the overall thrombus formation efficiency. Ultimately, only when the composite sponge possesses both interconnected surface pores and appropriately sized pores can the efficiency of blood concentration and thrombus formation be optimized, achieving rapid hemostasis. Therefore, combining SEM results and porosity analysis, SNPG0.2 and SNPG0.3 sponges exhibit the optimal pore structure.
[0114] Test Example 3A: Mechanical Properties (Compression Deformation) Test of Hemostatic Sponge
[0115] Compression tests were performed on the hemostatic sponges prepared in Examples 1-6 and the purchased sponges (Spirit absorbable gelatin sponge, wound care sponge, medical dental oral material, surgical emergency wound bleeding gel expandable sponge patch, type B: 20 mm*20 mm) using a TMS-Pro physical property analyzer (FTC Ltd, USA).
[0116] Before testing, accurately record the diameter and height of each sponge sample. Then, soak the sponge samples in deionized water for 30 minutes to allow them to fully absorb water. During testing, place the sponge horizontally on the test platform, set the compression rate to 10.0 mm / min, and record the pressure, strength, and sample morphology required at deformation rates of 40%, 50%, and 70%. Each group of samples was tested five times. The measurement results are as follows: Figure 5 .
[0117] like Figure 5 Under three different deformation rates, the compressive stress of SNPG sponges gradually increased with increasing gelatin content. This is because the more gelatin, the greater the cross-linking degree between shellac and gelatin, resulting in a larger polymer component and higher density, thus requiring greater stress. Meanwhile, the test results showed that under deformation rates of 40% and 50%, all tested SNPG sponges maintained their shape intact at the end of the test. However, under a deformation rate of 70%, except for SNPG0.2 and SNPG0.3 samples, the morphology of other SNPG sponges changed significantly. SNPG0.05, with a lower gelatin content, partially dissolved; SNPG0.1 collapsed into an amorphous state; while SNPG0.4, SNPG0.5, and SNPG0.6, with higher gelatin content, all cracked under pressure, and the higher the gelatin content, the more cracks appeared.
[0118] Experiment 3B: Water-triggered shape memory test of hemostatic sponge
[0119] Sponges with shape memory properties offer unique advantages in hemostasis, such as for narrow, irregular, and non-compressible wounds. To evaluate the water-triggered shape memory capability of SNPG sponges, the sponge's volume expansion rate was measured using the following method:
[0120] Volume expansion rate test method: Measure the original diameter R and original height h of the sponge sample using vernier calipers, and calculate the original volume V0 of the sponge according to the cylinder volume formula. Immerse the sponge sample in deionized water at 25℃ for 30 minutes, and again measure the diameter R1 and height h1 of the sponge sample after water absorption using vernier calipers. Calculate the volume V1 after water absorption. The ratio of V1 to V0 is the volume expansion rate of the sponge. The test results are as follows: Figure 6A .
[0121] To illustrate that the sponge sample can be prepared in various shapes to address irregular injuries to the body, the sponge sample prepared in Example 3 of this invention was cut into various shapes and then absorbed water. The shape of the water-absorbed sponge sample is as follows. Figure 6B .
[0122] Depend on Figure 6AIt can be seen that SNPG sponges exhibit a certain volume expansion after absorbing liquid, and the volume expansion rate decreases with increasing gelatin content. Specifically, there is no significant difference in volume expansion rate between SNPG 0.05 and SNPG 0.2 sponges, while the volume expansion rate of SNPG 0.3 (26.1%) is significantly lower than that of SNPG 0.2 (44.4%). This may be because the pore structure of the sponge decreases with increasing gelatin content. Good volume expansion allows the hemostatic sponge to fully absorb the liquid components in the blood, increasing the concentration of local blood cells and platelets, thus promoting thrombus formation. Furthermore, the volume expansion of the hemostatic sponge after absorbing liquid helps to create a local pressure effect, thereby achieving further hemostasis. In addition, SNPG 0.2 can be easily customized into various shapes to adapt to different wounds. Figure 6B These sponges maintain a volume expansion rate of 40.2% to 56.3% after absorbing liquid.
[0123] Test Example 3C: Performance Test of Volume Recovery Rate of Hemostatic Sponge After Liquid Absorption and Squeezing
[0124] Volume recovery rate: The sponge samples prepared in Examples 1-7 were immersed in deionized water for 30 min. The diameter R1 and height h1 of the sponge sample after water absorption were measured with vernier calipers. The initial volume V1 after immersion was calculated according to the cylinder volume formula. After measurement, a 100 g weight was placed on the sponge and pressed for 1 h. The sponge was then immersed in deionized water again for 30 min. The diameter R2 and height h2 of the sponge after water absorption were measured again. The volume V2 of the sponge after re-immersion was calculated according to the cylinder volume formula. The ratio of V2 to V1 is the sponge recovery rate. The test results are as follows: Figure 7A .
[0125] like Figure 7A As shown, except for SNPG0.5 which could not be restored to its original state due to partial dissolution, the volume recovery rate of the other sponges was all above 92%.
[0126] Experimental Example 3D: Cyclic Compression Performance Test of Hemostatic Sponge
[0127] The compressibility-recovery capability, i.e., cyclic compression performance, of the sponge was investigated using a TMS-Pro property analyzer (FTC Ltd., USA).
[0128] The SNPG0.2 sponge prepared in Example 3 and stored for 6 months, and the SNPG0.6 sponge prepared in Example 7, were soaked in deionized water for 30 min to fully absorb water. Then, cyclic compression tests were performed using a property analyzer. During the experiment, the sponge samples were allowed to fully absorb water before the next compression began after each compression. The diameter and height of the samples were accurately recorded for calculation. During the test, the samples were placed horizontally on the test platform, the compression rate was set to 10.0 mm / min, the deformation rate to 50%, and the number of cycles to 20. The test results are as follows. Figure 7B , 7C .
[0129] Depend on Figure 7B , 7C It can be seen that after 6 months of storage, SNPG 0.2 sponge still exhibits excellent shape memory function even after 20 repeated compressions, while SNPG 0.6 sponge with a higher gelatin content shows a continuous decrease in strain with increasing compression cycles (e.g., ...). Figure 7C Therefore, based on comprehensive analysis, SNPG0.2 exhibits the best mechanical properties among all sponges.
[0130] Experimental Example 4: Liquid Absorption Performance Test of Hemostatic Sponge Samples
[0131] The liquid absorption performance of sponge samples was tested in accordance with the People's Republic of China pharmaceutical industry standard YY / T 0471.1-2004 "Test methods for contact wound dressings - Part 1: Liquid absorbability".
[0132] The hemostatic sponges prepared in Examples 1-6 and the samples prepared in Control Examples 1 and 2 were pre-cut into small sponge samples of a certain volume, and their weights were weighed (denoted as W0). Then, the cut sponge sample samples were immersed in 15 mL of deionized water and 15 mL of rat blood containing sodium citrate anticoagulant (diluted 10 times with physiological saline) at 25℃ and 37℃, respectively, for 30 min. After immersion, one corner of the sponge sample after fully absorbing the solution was held with tweezers and suspended for 30 s before weighing the sponge sample after absorbing the solution (denoted as W1). The liquid absorption rate of the sponge sample was calculated according to formula (3).
[0133] (3)
[0134] Test results are as follows Figure 8A , 8B SN without added gelatin dissolves almost completely in water and blood, and has no ability to absorb liquids. For example... Figure 8AAll SNPG sponges made by adding gelatin to SNPG exhibit water absorption. SNPG 0.05 showed slight solid dissolution, with a water absorption rate of 961.9% at room temperature. SNPG 0.1 had the highest water absorption rate among the sponges, at 1247.9%. Subsequently, the water absorption rate gradually decreased with increasing gelatin content in the SNPG. This trend is consistent with the changes in water absorption rate. Figure 8B The blood absorption capacity of SNPG sponges also showed that with the increase of gelatin addition, blood absorption first increased and then decreased, with the blood absorption rate of SNPG 0.1 being 979.4%. Meanwhile, the temperature-dependent absorption performance test results showed that under normal body temperature of 37℃, the water absorption rate and salt solution absorption rate of the SNPG sponge samples were generally higher than those under room temperature conditions. This may be because the increased temperature makes the pores of the sponge larger, thus enhancing its liquid absorption capacity.
[0135] Test Example 4A: Test of the Liquid Absorption Rate of Hemostatic Sponge Samples
[0136] The time required for deionized water droplets to be absorbed by the sponge materials prepared in Examples 1-6 was recorded using the seated drop method with a contact angle meter. The test results are as follows: Figure 9 .
[0137] like Figure 9 As shown, the diffusion and absorption time of droplets on the surfaces of SNPG0.05, SNPG0.1, and SNPG0.2 sponges is less than 1 second. The hemostatic sponge of the present invention absorbs liquid blood rapidly and can absorb quickly. As the amount of gelatin added to the sponge increases, the time required for the droplets to diffuse completely and be absorbed gradually increases. The time required for the droplets on the surface of the SNPG0.5 sponge to diffuse completely and be completely absorbed is 27 seconds.
[0138] As a control, the commercial gelatin sponge had a water contact angle of 141.05°, exhibiting significant hydrophobicity. Without applying pressure, the time required for a droplet to completely diffuse and absorb on its surface was greater than 5 minutes. These experimental results demonstrate that the SNPG sponge prepared in this invention possesses suitable hydrophilic and hydrophobic properties, enabling it to absorb large amounts of blood in a very short time. Combined with its excellent liquid-triggered shape memory ability, it shows great application potential in treating massive bleeding caused by trauma or surgery.
[0139] Experimental Example 5: In vitro coagulation test of hemostatic sponge samples
[0140] The in vitro coagulation performance of SNPG sponges was evaluated using the blood coagulation index (BCI).
[0141] First, weigh 50.0 mg of each of the hemostatic sponge samples prepared in Examples 2-6 and place them in glass petri dishes. Simultaneously, use equal weights of medical gauze, commercial gelatin sponge, and SNG sponge prepared in Example 1 as controls. Accurately measure 9.0 mL of whole blood from citric acid-treated rats, add 1.0 mL of 0.2 mol / L CaCl2 solution to activate the rat blood, and drop 100 μL of activated rat blood onto the sample surface. Dissolve 100 μL of rat blood in 10 mL of deionized water as a blank sample group. After incubating the above samples at 37℃ for 3 min, add 10 mL of deionized water and incubate for another 10 min in a 37℃ oven. Then, remove the samples and rinse the uncoagulated blood with deionized water. Collect the rinsing fluid and measure the absorbance of the supernatant at 540 nm. All experiments were repeated 3 times. Calculate the coagulation index (BCI) according to formula (4), and the results are as follows. Figure 10A :
[0142] (4)
[0143] Take 900 μL of citric acid-treated rat blood and add 100 μL of 0.2 M CaCl2 solution to activate the rat whole blood. Accurately weigh a sponge (30 mg) and place it in a tube, add 200 μL of citric acid-treated rat whole blood, tilt the tube every 10 seconds, observe the blood flow, and record the blood clotting time. Repeat each sample three times and record the results as follows. Figure 10B .
[0144] like Figure 10A All SNPG sponges have a clotting effect, with SNPG 0.2 having the lowest clotting index at 10.5%, which is only half that of SNG sponges; Figure 10B The SNPG 0.2 sponge exhibited the fastest clotting rate among all tested samples, with a clotting time of only about 45 s, while the SNG sponge's clotting time was 70 s. As controls, the gauze and commercial gelatin sponge groups had BCI values greater than 85%, with clotting times of 324 s and 270 s, respectively, indicating poor clotting performance. These results suggest that adding an appropriate amount of PG can help improve the clotting effect of SNPG sponges.
[0145] Experimental Example 6: In vitro adhesion test of hemostatic sponges to erythrocytes
[0146] Fresh rat blood was centrifuged at 1000 rpm for 10 min, and the plasma was removed. The hemostatic sponge (SNPG0.2) prepared in Example 3 was cut into pieces of 0.5 cm × 0.5 cm × 0.5 cm. 50 μL of red blood cell suspension was dropped onto the sponge surface and incubated at 37°C for 10 min. Then, the sponge was washed with PBS to remove non-adherent red blood cells. All samples with adherent red blood cells were then transferred to 1.0 mL of deionized water and incubated at 37°C for 1 h to dissolve the adherent red blood cells. The absorbance of the resulting solution at 540 nm was measured.
[0147] In addition to using hemostatic sponge (SNPG0.2), gauze, commercial gelatin sponge, SNG sample prepared in Control Example 1, SN sample prepared in Control Example 2, and propyl gallate (PG) were used to conduct the red blood cell adhesion test.
[0148] The blank control group (also known as the reference group) consisted of red blood cell suspensions without sponge. Absorbance was measured, and each group was tested three times. The red blood cell adhesion rate (%) was calculated according to formula (5): The red blood cell adhesion rate test results are as follows: Figure 11 .
[0149] (5)
[0150] Meanwhile, the sponge with adhering red blood cells was fixed with 2.5% glutaraldehyde for 24 h, and then dehydrated with a series of fractionated ethanol solutions (50%, 70%, 80%, 90%, 100%) for 20 min. The sponge was then observed using a scanning electron microscope, and the results are as follows: Figure 12 .
[0151] Red blood cell adhesion test results as follows Figure 11 The erythrocyte adhesion rates of gauze and commercial gelatin sponge were 19.1% and 7.5%, respectively, significantly lower than those of SNPG sponge. The SN sample, without added gelatin and propyl gallate, also showed an erythrocyte adhesion rate of 54.9%, likely due to the electrostatic interaction between the positively charged ammonium salts of SN and erythrocytes. The erythrocyte adhesion rate of propyl gallate PG was 55.2%, comparable to that of SN in Control Example 2, possibly because the phenolic hydroxyl groups in its molecular structure reacted chemically with proteins. However, the erythrocyte adhesion rates of SNG and SNPG0.2 were 86.8% and 90.9%, respectively, significantly higher than the other groups, although there was no significant difference between them. This indicates that the cross-linking reaction of shellac and gelatin and the resulting network structure greatly promoted rapid erythrocyte adhesion and hematoxylin concentration.
[0152] The adsorption of red blood cells by the hemostatic material was further observed using scanning electron microscopy, and the results were as follows: Figure 12As shown in Figure A, only a few red blood cells were distributed on the long fibers of the gauze. After SNPG0.2 absorbed blood, it still retained its original continuous porous structure, and many red blood cells adhered and irregularly gathered in these pores. Most cells were observed to maintain a spherical shape (Figure B). As a control, propyl gallate powder also had good red blood cell adhesion, with red blood cells gathering on the surface and between the powder particles (Figure C). However, very few red blood cells were adsorbed on the commercial gelatin sponge (Figure D).
[0153] Experimental Example 7: Platelet Adhesion Test of Hemostatic Sponge
[0154] Freshly obtained rat blood was centrifuged at 1000 rpm for 10 min to collect platelet-rich plasma (PRP) for platelet adhesion assay.
[0155] The hemostatic sponge (SNPG0.2) prepared in Example 3 was cut into 0.5 cm × 0.5 cm × 0.5 cm pieces. 50 μL of PRP plasma was then added to each sponge sample, and the samples were incubated at 37°C for 30 min. The samples were then washed with PBS to remove non-adherent platelets. Adherent platelets were then dissolved in 1.0 mL of 1.0% Triton X-100 solution at 37°C for 1 h. Platelet lactate dehydrogenase activity was then measured using an LDH Kit according to the kit's instructions.
[0156] In addition to using hemostatic sponge (SNPG0.2), gauze, commercial gelatin sponge, SNG sample prepared in Control Example 1, SN sample prepared in Control Example 2, and propyl gallate (PG) were also used for platelet adhesion tests.
[0157] A 50 μL plasma sample that did not come into contact with the sample was used as a control group (also known as a blank control group). The absorbance was read at 450 nm using an ELISA reader. The platelet adhesion rate was calculated according to formula (6), and the test results are as follows. Figure 13 .
[0158] (6)
[0159] Platelet adhesion test results as follows Figure 13 Overall, the adhesion of the tested samples to platelets was basically consistent with the adhesion pattern of red blood cells. Among them, the platelet adhesion rates of SNG and SNPG0.2 were as high as 87.6% and 90.8%, respectively, which were significantly higher than other groups. The adhesion rates of gauze and commercial gelatin sponge, which served as controls, were only 18.3% and 20.2%, respectively.
[0160] Experimental Example 8: In vitro hemolysis test of hemostatic sponge samples
[0161] Rat blood was collected in a test tube containing sodium citrate anticoagulant. After thorough mixing, 1.0 mL of raw blood was diluted with 5.0 mL of physiological saline to obtain a blood sample for later use. 1.0 mg of each of the hemostatic sponges prepared in Examples 2-6 were weighed and incubated with 1.0 mL of physiological saline at 37°C for 12 h to obtain sponge sample suspensions. The suspensions were filtered, and the filtrates were collected. 100 μL of diluted blood was added to each filtrate and incubated at 37°C for 1 h. The suspensions were then centrifuged at 3000 rpm for 10 min, and photographs were taken. The supernatant was collected, and the absorbance of each liquid was measured at a wavelength of 540 nm.
[0162] The hemolysis test was conducted using the SNG sample prepared in Comparative Example 1, propyl gallate powder, gauze, and commercial gelatin sponge sample as controls.
[0163] Pure water and physiological saline without sponge were used as positive and negative controls, respectively. The hemolysis rate (%) was calculated according to formula (7):
[0164] (7)
[0165] Test results are as follows Figure 14A , 14B According to national standards, the hemolysis rate of a hemostatic sponge, as a hemostatic material, should be less than 5% to ensure safety. The blood compatibility of the hemostatic sponge was investigated through a hemolysis test. Figure 14B In pure water (positive control group), almost all red blood cells ruptured and released hemoglobin, resulting in a bright red solution; however, in the SNPG group sponge and other control groups, blood agglutination was observed, and the supernatant was lighter in color or even colorless. The hemolysis rate was measured... Figure 14A The hemolysis rate of all samples was less than 3.5%, meeting the safety standards for the application of hemostatic sponges. Figure 14A It can be seen that the hemolysis rate of SNPG 0.1~0.5 sponges with added propyl gallate is lower than that of SNG sponges without added propyl gallate, indicating that adding propyl gallate to sponges can reduce their hemolysis rate.
[0166] Experimental Example 9: In vitro cell compatibility test of hemostatic sponge
[0167] Cell expansion culture: NIH-3T3 cells (purchased from Guangzhou Huatuo Biotechnology) stored in liquid nitrogen were rapidly thawed in a 37°C water bath. After complete thawing, DMEM culture medium containing 10% FBS + 1% Ps was added to the cells to resuspend them. The thawed cell suspension was transferred to a 15 mL centrifuge tube in a sterilized laminar flow hood using a pipette. The tube was centrifuged at 1000 rpm for 5 min, the supernatant was discarded, and 1.0 mL of culture medium was added to resuspend the cells. This resuspended cell suspension was then transferred to a cell culture flask, and the culture medium was added to a final volume of 6.0 mL. The cells were cultured at 37°C with 5% CO2, and the medium was changed every other day. When the cells reached a certain density, they were passaged at a ratio of 1:2 or 1:3 and cultured again at 37°C with 5% CO2.
[0168] The effect of materials on NIH-3T3 cell proliferation activity was detected by the CCK8 assay.
[0169] The cells in the logarithmic growth phase were divided into groups of 1×10⁴ cells. 6 Cells were seeded at 100 μL / mL in 96-well plates. After cell adhesion, different concentrations (0, 10, 20, 30, 40, 50, 60 μg / mL) of material (sponge prepared in Example 3 and sponge prepared in Control Example 1) were added to the cell culture system. Each group was divided into 5 replicates. 24 h after treatment, 10 μL of CCK8 reagent was added to each well and incubated at 37°C for 3 h. The absorbance at a wavelength of 450 nm was measured, and the cell viability was calculated according to formula (8). The statistical analysis results are as follows. Figure 15 .
[0170] (8)
[0171] Where: As: absorbance of the experimental group (including cells, culture medium, CCK-8 solution and drug solution); Ac: absorbance of the control group (including cells, culture medium and CCK-8 solution, but excluding drug); Ab: absorbance of the blank group (including culture medium and CCK-8 solution, but excluding cells and drug).
[0172] To investigate the biocompatibility of sponges, the toxicity of sponge extracts to mouse embryonic fibroblasts (NIH-3T3) was tested. CCK-8 assay results showed that after incubation for 24 h at different sample concentrations, the survival rates of SNG and SNPG0.2 cells at various concentrations all exceeded 80%, indicating that the sponge samples are non-cytotoxic. Figure 15 .
[0173] Experimental Example 10: In vivo biocompatibility test of hemostatic sponge
[0174] Before the experiment, the sponge sample prepared in Example 3, the sponge sample prepared in Control Example 1, the commercial gelatin sponge, and propyl gallate (PG) powder were made into samples of the same shape and size (10 mm in diameter and 5 mm in height), and were sterilized under ultraviolet light for 3 h.
[0175] Fifteen male SD rats were randomly divided into five groups: a blank control group, a PG sample group, a commercial gelatin sponge group, a sponge SNG group, and a sponge SNPG group, with three rats in each group. All rats were anesthetized by intraperitoneal injection of 10% chloral hydrate solution (1.2 mL / 250 g). Subsequently, a small incision was made in the dorsal region of each rat. The prepared samples were implanted into the incision, and the skin was then closed. The incision without samples served as the blank control group. Seven days later, the rats were sacrificed, and the test samples and adjacent tissues were harvested. The obtained tissue samples were paraffin-embedded, sectioned, and mounted on glass slides. Acute and chronic inflammatory responses were detected using hematoxylin-eosin staining. The stained sections were observed and analyzed under a microscope. A stained section of the wound tissue seven days after sponge sample implantation is shown below. Figure 16A .
[0176] Depend on Figure 16A The results showed that after the prepared sponge samples were implanted into the dorsal incision of rats and the skin was closed, 7 days after implantation, the wound tissues of rats in the blank group, SNG, SNPG0.2, and PG groups showed almost no inflammatory response, but a large number of new blood vessels were present in the tissues, indicating that SNG and SNPG sponges have good biocompatibility and potential for in vivo application as biocompatible hemostatic agents. As a control, rat tissues implanted with commercial gelatin sponges showed a greater number of inflammatory cells.
[0177] Experimental Example 11: Antibacterial Performance Test of Hemostatic Sponge
[0178] Good antibacterial properties can prevent wound infection. The inhibitory effect of sponge on Staphylococcus aureus and Escherichia coli was investigated.
[0179] Staphylococcus aureus (ATCC25923) and Escherichia coli (ATCC-25922) were isolated and prepared into 10... 8 CFU suspensions were used to determine the in vitro antibacterial activity of four groups of samples: SN, SNG, SNPG0.2, and PG. 5.0 mg of sponge samples prepared in Control Examples 1, 2, and 3, as well as propyl gallate PG, were accurately weighed and placed in 20 mL centrifuge tubes. 1 mL of Luria-Bertani liquid medium and 10 mL of ... 8One CFU suspension was used, with Luria-Bertani liquid medium (without sample) as a blank control. Centrifuge tubes were incubated at 37°C aerobic conditions for 4 hours, using a shaker at 160 rpm to ensure uniform distribution. After incubation, the suspension was diluted 10 μL in PBS buffer. 5 The suspension was spread onto 30 μL of Luria-Bertani solid medium using the plating method. After incubation at 37°C under aerobic conditions for 24 h, individual colonies were counted. Figure 16B , 16C Both SNG and SNPG0.2 showed inhibitory effects on both types of bacteria. SNPG0.2 sponge exhibited inhibition rates of 72.9% against Staphylococcus aureus and 80.4% against Escherichia coli, with better antibacterial effects than SNG. This is because the PG component added to SNPG0.2 has a significant antibacterial effect, with an inhibition rate exceeding 99.9% against Escherichia coli. These results indicate that adding PG to sponge samples not only accelerates their coagulation efficiency but also enhances their antibacterial properties.
[0180] Experimental Example 12: In vivo hemostatic performance test of hemostatic sponge
[0181] The hemostatic properties of gauze, SNG, SNPG0.2, and commercial gelatin sponge in vivo were evaluated using rat femoral artery injury as a model of massive hemorrhage.
[0182] A femoral artery injury model was established using male SD rats to evaluate the hemostatic performance of the sponge. Before the experiment, all male rats were anesthetized intraperitoneally with 10% chloral hydrate solution (1.2 mL / 250 g) and fixed to surgical cork boards. When the femoral artery was injured, the rat's leg hair was shaved, the groin muscle was incised, and the femoral artery was exposed. A 20G needle was used to puncture the femoral artery, and the wound was exposed for 5 seconds to ensure normal bleeding. Immediately afterwards, a hemostatic sample with a diameter of 10 mm and a height of 5 mm was applied to the bleeding site, and the wound was manually pressed with medical gauze to stop the bleeding. The hemostatic samples included gauze, sponge samples prepared in Control Example 1 and Example 3, and commercial gelatin sponge. The hemostasis time was recorded until the wound stopped bleeding after the sponge was removed. The test results are as follows: Figure 17A , 17B .
[0183] like Figure 17A Compared with gauze and commercial gelatin sponge, SNG and SNPG0.2 immediately controlled severe bleeding, with average bleeding amounts of 345.7 mg and 251.6 mg in the treated rats, respectively. The bleeding amount in the NPG0.2 treatment group was significantly less than that in the SNG group (p < 0.05). Moreover, the bleeding amounts in both SNG and SNPG0.2 were significantly lower than those in the gauze and commercial gelatin sponge groups (801.0 mg and 652.7 mg, respectively) (p < 0.001).
[0184] like Figure 17B In terms of hemostasis time, both SNG and SNPG0.2 required significantly less time than the other two groups. Notably, the hemostasis time of SNPG0.2 with added propyl gallate was 107 s, while that of SNG was 183 s, showing a significant difference (p < 0.01); the bleeding volume in the SNPG0.2 treatment group was also significantly less than that in the SNG group.
[0185] The experimental results show that SNPG0.2 sponge has a good hemostatic effect on the femoral artery injury and massive bleeding model, and even has a significant advantage over gelatin sponges on the market. Therefore, it has great application potential in the fields of daily injury and surgical emergency.
[0186] The above embodiments of the present invention are merely exemplary and do not constitute any limitation on the scope of the present invention. Those skilled in the art should understand that modifications or substitutions can be made to the details and form of the technical solutions of the present invention without departing from the spirit and scope thereof, but all such modifications and substitutions fall within the protection scope of the present invention.
Claims
1. A method for preparing a hemostatic material, characterized in that, The steps are performed in the following order: 1) Prepare the shellac solution as follows: Add bleached shellac to an ammonia solution, heat, and stir to dissolve; the mass-volume concentration of the shellac solution is 0.05-0.2 g / mL; 2) Add gelatin to the shellac solution, heat, stir and dissolve to prepare a shellac-gelatin solution, wherein the volume ratio of the shellac solution to the mass of the gelatin is 10 ml: (0.2-0.3) g; 3) Add propyl gallate to the shellac-gelatin solution, stir and mix evenly to prepare a shellac-gelatin-propyl gallate mixed system. The propyl gallate is added to the shellac-gelatin network through hydrogen bonding to form a grid and porous structure. The amount of propyl gallate added is 20-100 mg per 10 mL of shellac-gelatin solution. 4) The shellac-gelatin-reinforcing agent mixture was freeze-dried to obtain a hemostatic material.
2. The preparation method according to claim 1, characterized in that, The amount of propyl gallate added in step 3) is 40 mg of propyl gallate per 10 mL of shellac-gelatin solution.
3. A hemostatic material, characterized in that, Prepared according to the method described in claim 1 or 2.